Effect of nitazoxanide on albendazole pharmacokinetics in cerebrospinal fluid and plasma in rats - María Isabel Ruiz-Olmedo; Iliana González-Hernández; Francisca Palomares-Alonso; Javier Franco-Pérez; María de Lourdes González F.; Helgi Jung-Cook (Elsevier, 2017)
Background: Although albendazole is the drug-of-choice for the treatment of neurocysticercosis, its efficacy is limited due to its low bioavailability. An alternative for optimizing pharmacological treatment is through drug combinations. In vitro studies have shown that nitazoxanide and tizoxanide (the active metabolite of nitazoxanide) exhibit cysticidal activity and that the combination of tizoxanide with albendazole sulfoxide (the active metabolite of albendazole) produced an additive effect. Objectives: (1) To assess the concentration profile of tizoxanide in plasma and in cerebrospinal fluid; and (2) to evaluate the influence of nitazoxanide on the pharmacokinetics of albendazole in plasma and in cerebrospinal fluid. Methods: Two different studies were conducted. In study 1, 10 male Sprague-Dawley rats received a single oral dose of 7.5 mg/kg of nitazoxanide and serial blood and cerebrospinal fluid samples were collected over a period of 4 h. In study 2, 38 healthy male Sprague-Dawley rats were randomly divided into two groups: one of these received a single dose of albendazole (15 mg/kg) and, in the other group, albendazole (15 mg/kg) was co-administered with nitazoxanide (7.5 mg/kg). Plasma and cerebrospinal fluid samples were collected from 0 to 16 h after administration. Albendazole sulfoxide and tizoxanide levels were assayed by using HPLC or LC/MS techniques. Results: In study 1, tizoxanide reached a maximum plasma concentration of 244.42 ± 31.98 ng/mL at 0.25 h; however, in cerebrospinal fluid, this could be detected only at 0.5 h, and levels were below the quantification limit (10 ng/mL). These data indicate low permeation of tizoxanide into the blood brain barrier. In study 2, Cmax, the area under the curve, and the mean residence time of albendazole sulfoxide in plasma and cerebrospinal fluid were not affected by co-administration with nitazoxanide. Conclusion: The results of the present study indicate that in rats at the applied doses, tizoxanide does not permeate into the cerebrospinal fluid. Furthermore, nitazoxanide does not appear to alter significantly the pharmacokinetics of albendazole in plasma or in cerebrospinal fluid.